A 10-bit 100-MS/s 5.23-mW SAR ADC in 0.18-μm CMOS. (August 2018) - Ma, Rui; Wang, Lisha; Li, Dengquan; Ding, Ruixue; Zhu, Zhangming
Abstract: A 10-bit 100 MS/s energy-efficient successive-approximation analog-to-digital converter (SAR ADC) is presented in this paper. In order to improve the conversion rate and reduce power consumption as well, a modified spilt-capacitor VCM -based switching scheme is proposed. By utilizing the LSB capacitors to obtain the last-bit, the proposed switching scheme could decrease the area of capacitive DAC. Moreover, by modifying the switching behaviors of the most significant bit (MSB) and 2 nd -MSB, the conversion rate could be improved. The prototype SAR ADC fabricated in 0.18 μm CMOS achieves 53.68 dB SNDR and 62.85 dB SFDR at 100 MS/s sampling rate. The active area of the core is 0.216 mm 2 . It consumes 5.23 mW with 1.8 V supply, resulting in a Walden figure of merit (FoM) of 123.2 fJ/conversion step.